Fra "en rigtig pige" til "en gravid mand" - Transpersoner og reproduktion: Den sidste grænse? - Heede, Dag (K&K - Kultur og Klasse, 2012)
From "A Real Girl" to "A Pregnant Man" | This article counterposes memoirs of a Danish transwoman, Lili Elbe, from the beginning of last century and an American transman, Thomas Beatie, from 2008. Elbe (1882-1931) changed sex in 1930 and hoped to complete her transition by becoming pregnant. A year later, however, she died. Beatie changed sex but wanted a child with his infertile female partner. He decided to stop his hormone treatments, get artificial insemination and carry a child, becoming the world's first "pregnant man". The two cases are documented in memoirs that both display longings for essence and purity and a fear of monstrosity and contamination. This essay discusses how genre and transsexuality work together to produce new notions of reproduction and naturalness.